Sosialisasi Upaya Pencegahan Stunting Pada Ibu Hamil Dengan Penerapan Gizi Seimbang - Suci Anggraeni; Marlince Baiyo; Mega Kuwandari; Nikita Wardani (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2024)
Stunting is a nutritional problem faced in the world, especially in poor and developing countries. Fulfilling balanced nutrition is one way to deal with stunting. It is important to stimulate the fulfillment of balanced nutrition since pregnancy so that pregnant women and their families can utilize food sources in preparing nutritious food for daily consumption. The aim of this community service activity is to socialize efforts to prevent stunting in pregnant women by implementing balanced nutrition. The target of this activity is pregnant women and mothers of productive age at Posyandu Kantil, Mojoroto Village. The activity consists of three stages, namely the preparation, implementation and evaluation stages. The activity begins with a pre-test to measure the respondent's level of knowledge using a questionnaire, continues with education, and ends with a post-test. The post test results showed that 80% of respondents had good knowledge and 20% had sufficient knowledge. Community service activities through education hope that participants will be motivated to maintain a diet with balanced nutrition, implement a healthy, nutritious daily menu that is adequate with local food resources as an effort to prevent stunting.